Shared paramyxoviral glycoprotein architecture is adapted for diverse attachment strategies. - Bowden, T; Crispin, M; Jones, E; Stuart, D (Portland Press for the Biochemical Society, 2010)
Members within the paramyxovirus subfamily Paramyxovirinae constitute a large number of highly virulent human and animal pathogens. The glycoproteins present on these viruses are responsible for mediating host cell attachment and fusion and are key targets for the design of antiviral entry inhibitors. In the present review, we discuss recent structural studies which have led to a better understanding of the various mechanisms by which different paramyxoviruses use their attachment glycoproteins to hijack specific protein and glycan cell-surface receptors to facilitate viral entry. It is observed that the paramyxovirus attachment glycoprotein consists of a conserved overall structure which includes an N-terminal six-bladed β-propeller domain which is responsible for cell receptor binding. Crystal structures of this domain from different biomedically important paramyxoviruses, including measles, Nipah, Hendra, Newcastle disease and parainfluenza viruses, alone and in complex with their functional cell-surface receptors, demonstrate three contrasting mechanisms of receptor engagement that paramyxoviruses have evolved to confer discreet protein- and glycan-receptor specificity. This structural information highlights the adaptability of the paramyxovirus attachment glycoprotein surface and the potential for the emergence of new and potentially harmful viruses in human hosts.